The neurovascular unit, matrix proteases, and innate inflammation - del Zoppo, Gregory J. (Ann N Y Acad Sci, 2010)
In the central nervous system, microvessel–neuron interactions appear highly coordinated. The rapid simultaneous responses of the microvasculature, neurons, and glia to focal ischemia in experimental ischemic stroke suggest that these responses could be viewed in a unitary fashion, rather than as individual components. The “neurovascular unit” consists of microvessels (endothelial cells–basal lamina matrix–astrocyte end-feet [and pericytes]), astrocytes, neurons and their axons, and other supporting cells that are likely to modulate the function of the “unit.” Each cell component generates an inflammatory response to ischemia. Matrix metalloproteinase (MMP)-9 was first associated with hemorrhagic transformation following focal ischemia in an experimental model. A series of studies of ischemic stroke patients also suggests a relationship between MMP-9 levels and several consequences of ischemic injury, including hemorrhagic transformation. Recent experimental work suggests specific cell sources for MMP-9 generation and for matrix proteases from four distinct families that could impact neurovascular unit integrity.